Problematika Peningkatan Keterampilan Muhadatsah di Pesantren Putri Miftahul Ulum Suren - Sofiatus Sobriyah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Education plays an important role in efforts to improve human quality, both social, spiritual and intellectual. Apart from that, education is not only burdened with the task of making the nation's life more intelligent, but it is also burdened with the task of fostering the nation's morals, namely upholding human values, all of which will be realized if it is based on religious beliefs. Meanwhile, religious belief will only be obtained with a deep understanding of the basics of religion itself. Judging from its function, language is a means of communication and liaison in everyday human interactions, both between individuals and individuals, individuals and society and society and certain nations. Likewise in Arabic, which has a special function compared to other languages. Not only does Arabic have high quality literature for those who know and understand it, but Arabic is also destined to be the language of the Koran, namely communicating the words of Allah (Yusuf, 1997: 187). Arabic language teaching has been implemented in formal and non-formal institutions, where the teaching is almost the same as the language as a whole. In fact, Arabic has become a special identity and characteristic of Islamic educational institutions, especially Islamic boarding schools, which differentiates them from other institutions. This is an important reason to research. Likewise with the existence of the Miftahul Ulum Suren Jember Islamic Boarding School whose vision and mission refer to the vision and mission of the Islamic boarding school. The Vision and Mission, among other things, seeks to develop students to become Muslims so that they become Muslims who are ready for life. For operationalization to achieve the output expected by the vision and mission, there needs to be a program realization at the girls' Islamic boarding school that must support it. One of the programs of the women's Islamic boarding school is the development of improving muhadatsah skills. From this program it is hoped that students will be able to speak Arabic actively. Because basically female students are able to perform muhadatsah optimally. The aim to be achieved in this research is to find out and describe the problems of improving muhadatsah skills at the Miftahul Ulum Suren Jember Islamic boarding school both in terms of implementation and evaluation. The research method used in this research is approach, determining research subjects, data collection methods (observation, interviews and data analysis.